Cyanobacteria - Tiwari, Archana (IntechOpen, 2018)
Cyanobacteria are photosynthetic microorganisms that inhabit almost all geographic locations, including oceans, caves, ponds, lakes, soil, snow, and hot springs. Their acumen to survive and succeed in a plethora of ambiance is due to their extraordinary metabolism and adaptations. Their wide applications include therapeutics, cosmeceuticals, wastewater remediation, biofuels, antioxidative enzymes, agriculture, and so on. This book highlights the important aspects pertinent to the fascinating world of cyanobacteria covering diverse topics such as electron microscopic dimension, cultivation, stress, and adaptations. This book provides insights into the world of tiny microbial factories and unravels the potentials for their futuristic innovative applications as precursors of drug molecules, eco-friendly renewable energy sources, remediation, and reservoirs of diverse value-added products for a better and brighter tomorrow.